2003
DOI: 10.1096/fj.02-1059fje
|View full text |Cite
|
Sign up to set email alerts
|

sAPP as a regulator of dendrite motility and melanin release in epidermal melanocytes and melanoma cells

Abstract: Numerous factors including ultraviolet (UV) radiation and growth factors regulate the specific function of epidermal melanocytes. A recently discovered epidermal growth factor is sAPP, the soluble N-terminal ectodomain of the beta-amyloid precursor protein (APP). Using whole mount preparations of isolated human epidermis, we detected a small population of basal cells, which expressed exceptionally high levels of APP. These cells were identified as melanocytes, which, similar to keratinocytes and neuronal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 52 publications
3
31
0
1
Order By: Relevance
“…To validate the assumed relationship between lamellipodia adhesion and ruffle formation, we applied the highresolution SACED cell motility assay [20,22,23] that allows to acquire and quantify various parameters of cell migration and motility simultaneously, and has been successfully used to characterize the motogenic activity of growth factors on epidermal keratinocytes and melanocytes [22,31]. To learn more about the signals and mechanisms involved in ruffle formation, we investigated the structural organization and the protein composition of membrane ruffles, and analyzed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the assumed relationship between lamellipodia adhesion and ruffle formation, we applied the highresolution SACED cell motility assay [20,22,23] that allows to acquire and quantify various parameters of cell migration and motility simultaneously, and has been successfully used to characterize the motogenic activity of growth factors on epidermal keratinocytes and melanocytes [22,31]. To learn more about the signals and mechanisms involved in ruffle formation, we investigated the structural organization and the protein composition of membrane ruffles, and analyzed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…sAPPa is an important growth factor in the development of the human brain and in adult neurogenesis, 12,18 paralleling its importance in other human tissues. 19,42 While the molecular mechanisms of its actions in postmitotic neurons remain unclear, sAPPa has been shown to exert a memoryenhancing effect. 43 Moreover, neural activity can lead to a higher secretion of sAPPa 44 and sAPPa has been shown to be neuroprotective against different types of insults.…”
Section: Biological Functions Of Sappamentioning
confidence: 99%
“…16 In vivo experiments have led to the hypothesis that AD may be caused in part by a lack of sAPPa, in addition to the toxic effects of Ab. 45 While it has been shown that sAPPa acts as an autocrine or paracrine growth or differentiation factor 18,19,42 and that it binds to defined patches on the cell surface, 46 no specific receptor for sAPPa has been identified so far. The availability of structural models of sAPPa may, therefore, provide tools for investigating the binding partners and mechanisms of action of this important APP fragment.…”
Section: Biological Functions Of Sappamentioning
confidence: 99%
“…Increased expression of amyloid protein family members can influence cancer development in several different tumour types (Nakagawa et al 1999, Meng et al 2001, Hansel et al 2003, Quast et al 2003, Baldus et al 2004, Ko et al 2004, Mauri et al 2005, Li et al 2006. Neuroblastoma, a malignant tumour of neural crest origin, is the only tumour type that has been reported to express high levels of APLP1 (Wasco et al 1992).…”
Section: Introductionmentioning
confidence: 99%